Blockchain Applications in Accounting and Auditing: A Review Article of Future Research Implications - Fadhil Saleh, Ahmed; Mushrif Rashid, Ahmed; Khalid Hindi, Waleed (BALANCE Economic Business Management and Accounting Journal, 2025)
Blockchain applications are important for accounting and auditing, as they have the opportunity to change transparency, security and efficiency in keeping financial records. This article examines today's research trends and future implications of blockchain use in these areas. Using learned articles from the Scopus database for bibliometric analysis, studies study research patterns, geographical references, thematic trends, collaboration networks and insights that can inform future research and policy on the effect of blockchain on accounting and revision practices. Recently, there has been a significant increase in publications, which reflects the growing interest in the region. The UK emerged as a pioneer in international cooperation, contributed significantly and maintained continuously. Keywords indicate increasing attention to integrating blockchain with large computer technologies to increase trends revision and accounting practices. Emerging subjects such as privacy and digital technology require more attention. Large publication sources included financial and credit activity: principle and behavioral problems and the International Journal of Digital Accounting Research. Research identifies major challenges in using blockchain technology in accounting and auditing, which includes ensuring security, establishing a regulatory structure and realizing the financial value. It recommends integrated management model, redesign the regulatory structure, and promotes responsible technological advances as AI for simplicity by using blockchain in these areas. Blockchain applications are important for accounting and auditing, as they have the opportunity to change transparency, security and efficiency in keeping financial records. This article examines today's research trends and future implications of blockchain use in these areas. Using learned articles from the Scopus database for bibliometric analysis, studies study research patterns, geographical references, thematic trends, collaboration networks and insights that can inform future research and policy on the effect of blockchain on accounting and revision practices. Recently, there has been a significant increase in publications, which reflects the growing interest in the region. The UK emerged as a pioneer in international cooperation, contributed significantly and maintained continuously. Keywords indicate increasing attention to integrating blockchain with large computer technologies to increase trends revision and accounting practices. Emerging subjects such as privacy and digital technology require more attention. Large publication sources included financial and credit activity: principle and behavioral problems and the International Journal of Digital Accounting Research. Research identifies major challenges in using blockchain technology in accounting and auditing, which includes ensuring security, establishing a regulatory structure and realizing the financial value. It recommends integrated management model, redesign the regulatory structure, and promotes responsible technological advances as AI for simplicity by using blockchain in these areas.